Interleukin (IL)-6, tumour necrosis factor alpha (TNF-α) and soluble interleukin-2 receptors (sIL-2R) are elevated in patients with major depressive disorder: A meta-analysis and meta-regression - Liu, Yang; Ho, Roger Chun-Man; Mak, Anselm (Journal of affective disorders, 2012)
Many studies have explored the association between soluble interleukin-2 receptor (sIL-2R), cytokines and major depressive disorder (MDD). However, the results of these studies were not consistent. The aim of our study is to compare the levels of sIL-2R and cytokines in the blood between MDD patients and controls by a meta-analysis and to identify moderators accounting for potential heterogeneity in the levels of sIL-2R and cytokines in MDD patients versus controls by meta-regression analyses. A comprehensive literature search was performed to identify studies comparing the levels of sIL-2R and cytokines between MDD patients and controls. We pooled the effect sizes for standardized mean differences (SMD) of the levels of sIL-2R and cytokines. We also performed meta-regression and sensitivity analyses to investigate the roles of age, gender, sample type, ethnic origin and selected studies' quality in explaining potential heterogeneity and differences in results respectively. Twenty-nine studies were selected for this analysis. The levels of sIL-2R, TNF-α and IL-6 in MDD patients were significantly higher than those of healthy controls (SMD=0.555, p<0.001, SMD=0.567, p=0.010; SMD=0.680, p<0.001). Mean age of all subjects was a significant moderator to explain the high heterogeneity of IL-6. Sensitivity analysis found that European but not non-European subjects have higher levels difference of sIL-2R, TNF-α and IL-1β between MDD patients and controls. The severity of MDD was not considered. The blood levels of sIL-2R, TNF-α and IL-6 were significantly higher in MDD patients than controls. Age, samples source and ethnic origins may play a potential role in heterogeneity.